PENYULUHAN “ISI PIRINGKU” UNTUK PENINGKATAN IMUNITAS ANAK DESA KARANG BUNGA - Miranti, Rizka Mulya; Lestari, Yulianita Pratiwi Indah; Mulyani, Tuty; Fajeriyati, Nurul; Rahmawati, Rahmawati; Mustharah, Mustika; Salsabilla, Syifa Aulia; Sazidan, Akhbar Arya Jouraist; Sari, Cindy Fransiska; Amalia, Rizka; Safitri, Salsabila Nurlaila (LP2M STP Mataram, 2024)
Many children only want to eat the foods they like, such as sweet, salty, or high-carbohydrate foods, while vegetables and fruits are often ignored. This unbalanced diet can lead to children lacking essential nutrients needed to maintain immunity and optimal growth.